Pengelolaan dan Manajemen Usaha Produk UMKM menuju Kemandirian Ekonomi Masyarakat Desa - Katili, Muhammad Rifai; Lahay, Sri Nilawati; Amali, Lanto Ningrayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The guidance and development of Micro, Small, and Medium Enterprises (MSME) is an effort by the government, academia, business world, and community. The goal is to realize an economically independent village that upholds the local wisdom of the community as an active participatory actor in the management of MSME product businesses with specific targets are: (1) increasing community business awareness through socialization and training on the management of MSME products in rural communities; (2) the realization of the management of MSME product businesses and product marketing of MSME actors; and (3) the realization of household businesses that managed independently. This activity method is a workshop method in the form of training and assistance to the community through intensive training on the management of MSME product businesses to achieve all expected targets and outputs through the implementation of Thematic KKN activities. This activity results in increase in the understanding and involvement of MSME business actors by promoting, improving administration, improving product packaging, and selling online. In addition, MSME business actors can learn how to manage a good business to improve the economy of the MSME business community.